Dry and Wet Spell Probability by Markov Chain Model and its Application to Crop Planning in Doimukh (Itanagar), Arunachal Pradesh - Dabral, P.P.; Jhajharia, Deepak (Journal of Soil and Water Conservation, 2022)
In this paper attempt has been made to estimate dry and wet spell probability using Markov Chain Model for Doimukh (Itanagar), Arunachal Pradesh. Probability of occurrence of dry week is higher from week no. 1 to 12 and also from week no. 43 to 52. The range of probability of occurrence of dry week in these weeks varies from 42.8 to 100 per cent. Probability of occurrence of wet week is higher from week no. 15 to 41. The range of probability of wet week varies from 64 to 100 per cent. Week no. 1 to 6 and 43 to 52 of the year remains under stress on an average, as there are 50 to 92.8 per cent chances of occurrence of 2 consecutive dry weeks. The analysis showed that monsoon starts effectively from 23rd week (4th June to 10th June) in Doimukh. The 25th week (18th June to 24th June) is ideal time for initiation of wet land preparation of rice field for short duration variety. On 15th week sowing of summer maize (rainfed) may be done. The 19th week (7th May to 13th May) is ideal time for initiation of wet land preparation of rice field for long duration variety